Case studies of the practice of nomination and hibah by Malaysian Takaful Operator - Abdullah, Nurdianawati Irwani; Abdul Aziz, Nazliatul Aniza (ipublication, 2010)
Nomination is a process whereby a policyholder who purchases the insurance policy should name someone to benefit from the policy in the event of the policyholder's death.Nomination is purposely performed to ensure the beneficiaries receive the takaful benefits promptly.The current practice of the nomination clause in family takaful operation is basically vague because the Takaful act 1984 does not expressly provide any rule to that effect.This study aims to examine the status of nominees for Muslim participants and non-Muslim participants in family takaful as stipulated in the takaful nomination form. it is significant to clarify the status of the nominee, either as a beneficiary or an executor, in order to avoid any misconception among the legal heirs in the future. besides this, the study also seeks to assess how far the related concept of hibah to the nomination in family takaful is currently implemented by the takaful operators in Malaysia.Hibah seems to be an alternative for Muslim participants to allocate the takaful benefits to the right beneficiaries without adhering to the Islamic law of inheritance (fara'it).This study adopts the document analysis to identify whether the takaful nomination form is standardised and clarified in respect of the status of the nominee for each takaful operator in Malaysia.Samples of eight licensed takaful.